Nursing and Integrative and Complementary Health Practices: an integrative review (Research, Society and Development, 2020)
Objective: to identify the existing scientific production about nursing in the context of Integrative and Complementary Health Practices. Method: This is an Integrative Literature Review study, carried out in March 2020, in the databases: Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Literature in Health Sciences and Nursing Database, using the words "Complementary Therapies", "Alternative Therapies", "Integrative and Complementary Practices" and "Nursing". The sample consisted of 12 articles. Results and Discussion: Four thematic categories emerged: Health professionals' knowledge about PICS; Nurse's performance in PICS; Use of PICS in the treatment of chronic diseases; and PICS approach during undergraduate nursing. Conclusion: When identifying in the existing scientific production about PICS, it was realized the relevance of the care provided, especially with regard to increasing the quality of life of patients undergoing this practice. In addition, despite the proven scientificity of several PICS, there is still a lot to evolve, with regard to practice by professionals, especially nurses.